The Cost and Benefits of Tax Treaties with Investment Hubs : Findings from Sub-Saharan Africa - Beer, Sebastian; Loeprick, Jan. (Washington, D.C. : International Monetary Fund, 2018)
This paper investigates the costs and benefits of concluding double tax treaties with investment hubs. Based on a sample of 41 African economies from 1985-2015, the results suggest that signing treaties with investment hubs is not associated with additional investments; yet, these treaties tend to come with nonnegligible revenue losses. Building on a theoretical model, the paper investigates the role of treaty shopping in driving nominal investment flows and provides indirect evidence for its importance in the sample.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet